Інтерполяційні інтегральні операторні дроби в банаховому просторі - Макаров, В.Л.; Хлобистов, В.В.; Демків, І.І. (Видавничий дім "Академперіодика" НАН України, 2008)
For the first time, the interpolation operator integral chain fractions on continual knots are studied for nonlinear operators which are defined on linear topological spaces.